Demografia dos Desastres: um estudo para populações em áreas de risco de rompimentos de barragem em Nova Lima, Minas Gerais - Vanessa Campos de Oliveira Soares (2020)
After two major disasters, Samarco (2015) and Vale (2019), and given the potential for further dam disruptions, the need to discuss territorial management of this type of hazard was highlighted. Acknowledge about populations living in risk areas is an essential part of this process. Using as a case study the B3/B4 tailing dam, located in the district of São Sebastião das Águas Claras, Nova Lima, Minas Gerais, this work has as central objective the identification of singularities and factors that contribute to the elaboration of a conceptual framework on population vulnerability to the risk of tailing dam collapse, through an approach wich has focus on the perception of individuals and the social representation of the objects of this study. Between January and February 2020, 20 indepth interviews were conducted with residents of different regions of the risk area of the B3/B4 tailing dam and its surroundings. The Free Words Association Technique (TALP) was used to collect data on evocations related to the two terms under investigation: risks and dams. Two social representation analysis approaches were adopted: the Theory of the Central Nucleus and Network Analysis, which were associated with the analysis of indepth interviews. The association between these analysis techniques allowed the identification, in the interviewees' discourse, of not only the meaning associated with the mentioned evocations, but also the existing relationships between them and relevant aspects for the conformation of vulnerability. The results indicate that, for populations in areas at risk of collapse, the collective representations of both terms present evocations related to negative feelings, such as "fear" and "uncertainty" as elements of greater centrality. Among the factors that influence the social representation of the risk and the dam are: the location of the domicile in relation to the tailing dam, the performance of the mining company and public authorities in the region, the social capital, the mobilization capacity of society, the forms of negotiation and popular participation. These factors can influence the individuals' ability to adapt and respond to this new risk situation. The identified impacts resulting from the risk situation also corroborate the view of disasters as social processes under construction, while the rupture of the tailing dam would represent a catastrophic event.